2022
DOI: 10.1128/spectrum.01186-22
|View full text |Cite
|
Sign up to set email alerts
|

An Insight into the Endophytic Bacterial Community of Tomato after Spray Application of Propiconazole and Bacillus subtilis Strain NBRI-W9

Abstract: Endophytes are plant inhabitants acting as its extended genome. The present study highlights the importance of maintaining plant endophytes for sustainable disease resistance in plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 70 publications
0
3
1
Order By: Relevance
“…Even with the systemic fungicide Banner Maxx, after being sprayed onto plant foliage, it first acted on the surface bacteria until it penetrated into internal tissue; this effect was dependent upon the length of time required to penetrate and the percentage of material that entered the tissue. However, the limited effect of the systemic fungicide on boxwood endophytes is different from that reported by Yadav et al ( 37 ). Under greenhouse conditions, they showed that 0.1% propiconazole had a suppressive effect on the growth of culturable bacterial endophytes isolated from tomato leaves.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…Even with the systemic fungicide Banner Maxx, after being sprayed onto plant foliage, it first acted on the surface bacteria until it penetrated into internal tissue; this effect was dependent upon the length of time required to penetrate and the percentage of material that entered the tissue. However, the limited effect of the systemic fungicide on boxwood endophytes is different from that reported by Yadav et al ( 37 ). Under greenhouse conditions, they showed that 0.1% propiconazole had a suppressive effect on the growth of culturable bacterial endophytes isolated from tomato leaves.…”
Section: Discussioncontrasting
confidence: 82%
“…In contrast, the mechanisms by which propiconazole might affect bacteria are unclear because bacteria lack the fungal cell wall structure for the fungicide to act on as an ergosterol biosynthesis inhibitor ( 57 ). However, propiconazole used at a higher concentration is known to adversely impact bacterial communities in plants ( 37 ) or soil ( 29 ). Our results indicate, however, that propiconazole used at the label rate has relatively little impact on the surface-colonizing bacteria, although this rate is effective for controlling the boxwood blight pathogen ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the bacterial digestion of starch, sucrose metabolism, biosynthesis of amino acids, phytohormones, and intermediate compounds of vital biochemical cycles are metabolic activities that promote the development of plants from germination to advanced phenological stages ( Hunting et al., 2015 ; Cui et al., 2019 ; Rehman et al., 2019 ; Yuan et al., 2021 ; Mishra et al., 2022 ). Finally, the biosynthesis of antibiotic compounds such as streptomycin, cephalosporin, tetracycline, polyketides, and non-ribosomal peptides such as siderophores can function as antifungals and protect the seed before and during germination and early growth ( Abbas et al., 2022 ; Huang B. et al., 2022 ; Yadav et al., 2022 ), although they could also interfere with the establishment of mutualistic mycorrhizae ( Schrey et al., 2012 ).…”
Section: Discussionmentioning
confidence: 99%